1998
DOI: 10.1128/jvi.72.8.6922-6928.1998
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Structure of Human Respiratory Syncytial Virus Fusion Glycoprotein

Abstract: New series of escape mutants of human respiratory syncytial virus were prepared with monoclonal antibodies specific for the fusion (F) protein. Sequence changes selected in the escape mutants identified two new antigenic sites (V and VI) recognized by neutralizing antibodies and a group-specific site (I) in the F1 chain of the F molecule. The new epitopes, and previously identified antigenic sites, were incorporated into a refined prediction of secondary-structure motifs to generate a detailed antigenic map of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(40 citation statements)
references
References 44 publications
4
31
0
5
Order By: Relevance
“…Although we do not know the exact nature of the antigenic precursor source of epitope F249-258, it must include a portion of the F protein harbouring the epitope, which is interestingly located near important antigenic sites for neutralising antibodies. 24 Our findings have important implications for RSV vaccine studies as they open the possibility of priming RSV-specific CTLs and antibodies with a non-infectious agent.…”
Section: Cross-priming Of Cd8 þ T Lymphocytes Specific For F249-258 Imentioning
confidence: 74%
“…Although we do not know the exact nature of the antigenic precursor source of epitope F249-258, it must include a portion of the F protein harbouring the epitope, which is interestingly located near important antigenic sites for neutralising antibodies. 24 Our findings have important implications for RSV vaccine studies as they open the possibility of priming RSV-specific CTLs and antibodies with a non-infectious agent.…”
Section: Cross-priming Of Cd8 þ T Lymphocytes Specific For F249-258 Imentioning
confidence: 74%
“…Structures of F proteins complexed with neutralizing antibodies have been solved for a number of pneumo-and paramyxovirus family members including RSV (Figure 3), HPIV3, and NiV. Distinct antigenic sites were identified on RSV F (Figure 4): conformation-dependent site Ø that is located at the apex of prefusion F and a dominant target for nAbs [36,[76][77][78]; sites II and IV that are present in both the pre-and postfusion F conformations [67,79]; site III that likewise exists in both F conformations, but undergoes rearrangement of secondary structure elements forming the epitope [80,81]; site V located between sites Ø and III on prefusion F [82,83]; and post-fusion F site I [84,85]. A cryo-EM structure of HPIV3 F complexed with nAb PIA174 likewise locates the binding site to the apex of the prefusion F trimer, establishing contact with residues of all three F protomers [37].…”
Section: Druggable Sites and Neutralizing Epitopesmentioning
confidence: 99%
“…Beeler et al [35] have identified multiple neutralizing epitopes on RSV F protein using competitive binding assays with a panel of RSV F monoclonal antibodies and monoclonal antibody resistant mutant (MARMs) and subsequently, antigenic sites I, II, IV, V and IV were mapped on RSV F [36]. A competitive ELISA was performed using monoclonal antibodies 1107, 1112, 1153, 1243 to identify neutralizing antibodies induced by the RSV F vaccine.…”
Section: Competitive Binding Of Vaccine-induced Antibody To Other Rsvmentioning
confidence: 99%